Safe System in Practice: A Study of Practitioner Awareness, Support and Implementation - Michael Green; Carlyn Muir; Jennie Oxley; Amir Sobhani (Journal of Road Safety)
In 2004, Australian jurisdictions adopted the Safe System approach to address road trauma. This approach seeks to prevent crashes on the road through harm minimisation principles that include a shared responsibility for safety. As an early adopter, the Victorian Government has encouraged practitioners, through guidance material and public policy, to implement Safe System. Yet, limited information exists regarding the degree of awareness of, or support for, the Safe System by individuals, whose role it is to influence and create the road safety outcomes expected by society. To understand practitioner awareness, perceptions and implementation of Safe System, an online survey was developed. Findings from completed surveys (n=469) indicate that one quarter of practitioners were unaware of the Safe System concept. Practitioners who had heard of Safe System, broadly agreed with the approach and believed that it positively contributed to their work. Importantly, practitioners believed that they were implementing Safe System and were likely to continue to do so in the future. A small subset of practitioners was not supportive of the approach, which alongside the low levels of awareness presents an additional challenge to policy implementation. Victoria’s experience highlights to other jurisdictions seeking to apply Safe System that active and sustained engagement with practitioners is required to ensure they are aware of the concept, collectively understand it and are clear when, where and how it is to be implemented.